Penerapan Lesson Study pada Perkuliahan Pengantar Aljabar - Marfi Ario (Universitas Maritim Raja Ali Haji, 2019)
The quality of learning is an important thing that must be the attention of lecturers. The quality of learning can be improved through collaboration between lecturers in the implementation of lesson study. This research aims to describe the implementation of lesson study in introductory algebra. This research is a descriptive qualitative study. The research subjects were first semester students of mathematic education consisting of 27 students. Data collected in form of students learning outcomes and learning process data in the implementation of lesson study. Data collection thechniques in the form written tests, observation, discussion, and video documentation. Test data analysis was carried out by giving a score to the test results, while the learning activities data were analyzed by describing the implementation of learning. The result of the study show that the implementation of lesson study which consists of the plan, do, and see stages has been well implementated. Student learning outcomes also show good results